2008
DOI: 10.5194/angeo-26-3885-2008
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of auroral Langmuir waves

Abstract: Abstract. The Physics of Auroral Zone Electrons II (PHAZE II) sounding rocket was launched in February 1997 into active pre-midnight aurora. The resulting high frequency wave data are dominated by Langmuir waves. Consistent with many previous observations the Langmuir waves are sporadic, occurring in bursts lasting up to a few hundred ms. We compute statistics of the electric field amplitudes of these Langmuir waves, with two results. First, the shape of the distribution of running averages of the electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 52 publications
5
8
0
Order By: Relevance
“…For a random distribution of γ i and/or δt i , log S will have a normal distribution, according to the central limit theorem. Such distributions have already been observed in the intensity of terrestrial auroral Langmuir waves [ Samara et al , 2008] or visible emissions [ Shefov et al , 2006]. The above results establish that this also the case for the CMI instability.…”
Section: Akr Stokes Parameterssupporting
confidence: 82%
“…For a random distribution of γ i and/or δt i , log S will have a normal distribution, according to the central limit theorem. Such distributions have already been observed in the intensity of terrestrial auroral Langmuir waves [ Samara et al , 2008] or visible emissions [ Shefov et al , 2006]. The above results establish that this also the case for the CMI instability.…”
Section: Akr Stokes Parameterssupporting
confidence: 82%
“…Therefore these distributions are intrinsic to the waves. Statistical analyses of the waveform distributions for auroral Langmuir waves, 44 and of both the waveform and envelope distributions for Langmuir waves in the cusp region, 32 showed that time averaging has significant effects on the distributions. For in- stance, LaBelle et al 32 found that sufficient averaging leads to lognormal distributions for both P͑log E͒ and P e ͑log E e ͒, in contrast to the power-law forms in the absence of averaging.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of statistical analyses of the wavefields are considered here: statistics of the absolute values of the wavefields and statistics of the envelopes of the fields. The former are the type presented by Samara et al [2008] for the case of nightside auroral Langmuir waves detected during the PHAZE II rocket experiment. The latter are the type applied to Langmuir waves in the electron foreshock [ Cairns and Robinson , 1997, 1999], solar type III source regions [ Robinson et al , 1993], and the auroral magnetosphere [ Cairns and Menietti , 2001].…”
Section: Data Presentationmentioning
confidence: 86%
“…Another previous study relevant to the observations reported below is a recent statistical analysis of waveforms of auroral Langmuir wave packets observed with the PHAZE‐2 rocket, launched into active nighttime aurora [ Samara et al , 2008]. Inspired by statistical analyses of Langmuir wave packets in Earth's electron foreshock [ Cairns and Robinson , 1997, 1999], Samara et al [2008] compute histograms of log N versus log E for nine selected 2–13 s intervals of Langmuir wave activity, where N is the number of measurements for each value of wave electric field E . Averaging the wavefields over varying time intervals reveals a transition in the shapes of the resulting histograms for averaging times of 50–100 μ s, although the data have insufficient resolution to determine the cause of this transition.…”
Section: Introductionmentioning
confidence: 99%